A preliminary analysis of horizontal upper body pushing and pulling strength ratios in elite male athletes - Appleby, B.; Hori, N. (Journal of Science and Medicine in Sport, 2011)
Introduction: Balance between opposing muscle groups has long been encouraged to prevent muscle injury (eg. External to internal shoulder rotator cuff, hamstring to quadriceps). The purpose of this investigation was to quantify the opposing horizontal pulling and pushing strength ratios in male athletes from rugby union (RU) and water polo (WP) using common field based tests. Methods: A 1 repetition maximum (1RM) bench press (BPr), bench pull (BPl) and a concentric-only BPr (CBPr) were used to assess horizontal pulling and pushing strength over three separate testing occasions within a week. Six elite RU players (23.1 ± 3.1 years and 108 ± 9kg) and seven semi-elite WP players (21.2 ± 4.6 years and 89 ± 16.6 kg) were familiar with the tests. The BPl exercise requires the lifter lie in a prone position on a high bench and pull a bar from the floor to the underside of the bench in a concentric only action. While BPr consists of eccentric and concentric action, there is no eccentric phase in BPl. To make a valid comparison between BPl and BPr, a CBPr was included in the testing. Strength ratios (BPr/BPl x 100 and CBPr/BPl x 100) and correlations were analysed in each sport separately, thus it allows us to discuss specific adaptations to the demands of respective sport. Results: The 1RM BP, BPl and CBPr for RU were 141.7 ± 10.3kg, 107.5 ± 7.6kg and 122.1 ± 5.1kg and for WP were 94.6 ±22.2kg, 84.3 ± 15.3kg, and 92.1 ± 20.2kg respectively. The BPr:BPl and CBPr:BPl ratio was 132% ± 6% and 114% ± 6% for RU and 112% ± 11% and 109% ± 9% for WP respectively. The correlations between BPr, BRl, and CBP ranged from r=0.94 to 0.98. Conclusion: RU player demonstrated far superior absolute 1RM upper body strength compared to WP. However, the WP demonstrated a more balanced push to pull ratio of the upper body. The combative nature of RU requires pushing of opponents and withstanding impact forces during tackling. In WP, the aquatic environment does not permit such application of force. Whilst pushing and pulling strength training tends to be equally prescribed in RU, the injury risk to the shoulder in WP, from throwing and swimming, requires additional prescription of pulling exercises for the posterior muscle groups. This might explain the smaller BPr/BPl and CBPr/BPL ratio of WP players.